2011
DOI: 10.4236/ajac.2011.24057
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Rapid Extracellular Biosynthesis of Silver Nanoparticles Using Carom Seed (Trachyspermum copticum) Extract and in Vitro Studies

Abstract: Microwave-assisted rapid extracellular biosynthesis of silver nanoparticles was carried out by using carom seed (Trachyspermum copticum) extract as the reducing agent. The reaction mixture containing AgNO 3 and carom seed extract when exposed to microwave irradiation resulted in reducing silver ions to bio-functionalized silver nanoparticles of size 6-50 nm. The AgNP were characterized by UV-vis spectroscopy (UV-vis), X-ray diffraction (XRD), energy dispersive X-ray analysis (EDAX), field emission scanning ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 21 publications
2
17
0
1
Order By: Relevance
“…Silver nanoparticles prepared using Trachyspermum copticum seed has scavenged the DPPH free radical five times more effectively than butylated hydroxy anisole (BHA) at the maximum concentration of 10 g/mL. The percentage of DPPH quenching effect was found to be increased with increasing concentration of silver nanoparticles from 2.5 to 10 g/mL (Raghunandan et al, 2011b). Interestingly, Mittal et al (2012) have reported that phenolic compounds capped silver nanoparticles (synthesized from the flower extract of Rhododendron dauricum) were found to be potent free radical scavenger than the standard, Trolox.…”
Section: Antioxidant Activity Of Plant Extract Synthesized Silver Nanmentioning
confidence: 90%
See 4 more Smart Citations
“…Silver nanoparticles prepared using Trachyspermum copticum seed has scavenged the DPPH free radical five times more effectively than butylated hydroxy anisole (BHA) at the maximum concentration of 10 g/mL. The percentage of DPPH quenching effect was found to be increased with increasing concentration of silver nanoparticles from 2.5 to 10 g/mL (Raghunandan et al, 2011b). Interestingly, Mittal et al (2012) have reported that phenolic compounds capped silver nanoparticles (synthesized from the flower extract of Rhododendron dauricum) were found to be potent free radical scavenger than the standard, Trolox.…”
Section: Antioxidant Activity Of Plant Extract Synthesized Silver Nanmentioning
confidence: 90%
“…Moreover, they have also capped around the synthesized nanoparticles, thus providing stability as well as biocompatibility. Recent studies have shown that the phytochemicals such as proteins ( Prabakar et al, 2013;Prakash et al, 2013;Santhoshkumar et al, 2011), flavonoids (Elavazhagan and Arunachalam, 2011;Philip, 2011;Raghunandan et al, 2011a;Subba Rao et al, 2013), polyphenols (Antony et al, 2011;Jeyaraj et al, 2013a;Kumar et al, 2010;Mohan Kumar et al, 2012;Njagi et al, 2011;Raghunandan et al, 2011b;Rodríguez-León et al, 2013;Roni et al, 2013;Sahu et al, 2013;Suganya et al, 2013), alkaloids (Vijayaraghavan et al, 2012), saponins (Geethalakshmi and Sarada, 2012), phenols (Lukman et al, 2011;Sathishkumar et al, 2012), essential oils (Vijayaraghavan et al, 2012), and polyols Veerasamy et al, 2011) present in the plant extracts were reported to play a major role in the bioreduction of silver ions and capping of the synthesized nanoparticles (Table 1).…”
Section: Possible Phytochemicals/phytoconstituents Responsible For Thmentioning
confidence: 97%
See 3 more Smart Citations